Autoantibodies against myelin oligodendrocyte glycoprotein in a subgroup of patients with psychotic symptoms - Nikita A. van de Burgt; Nikita A. van de Burgt; Laila Kulsvehagen; Marina Mané-Damas; Marina Mané-Damas; Luc Lutz; Anne-Catherine Lecourt; Clara Monserrat; Clara Monserrat; Anita M. Vinke; Cem İ. Küçükali; Shenghua Zong; et al. (Frontiers in Neurology)
The presence of autoantibodies against myelin oligodendrocyte glycoprotein (MOG) is a hallmark of MOG antibody-associated disease (MOGAD), a recently defined demyelinating disease entity presenting with core clinical features of optic neuritis, myelitis, and acute disseminated encephalomyelitis. Although MOG antibodies have also been described in a small number of patients with other conditions, including mental disorders, their prevalence and clinical specificity in patients with isolated psychotic symptoms remain unclear. Here, we screened sera from 262 patients with at least one psychotic episode and 166 control subjects for the presence of MOG antibodies of the immunoglobulin G (IgG) isotype with a live cell-based assay. Serum reactivity to additional antigens was assessed by immunohistochemistry. Four patients, representing 1.5% of the patient cohort, and one control individual, representing. 0.6% of the healthy control cohort, were seropositive for MOG-IgG antibodies. Of the four MOG-IgG seropositive patients, three experienced visual hallucinations. Overall, MOG antibodies were detected at a low frequency in patients with psychotic episodes. While we cannot exclude the possibility of false-positive results or seroconversion due to secondary myelin damage, the association with visual hallucinations in three out of four MOG-IgG seropositive patients may point toward an underlying autoimmune etiology.